EFFECT OF TESTOSTERONE REPLACEMENT ON EPITHELIAL AND STROMAL TISSUE IN PROSTATIC LOBE IN ORCHIDECTOMIZED WISTAR - Irawan, Yudi; Sihombing, Aaron T. (Indonesian Urological Association, 2013)
Objective: To evaluate the effect of testosterone replacement on epithelial and stromal changes of prostatic lobes in castrated wistar rats. Material & Method: The subjects were 30 wistars equally assigned to castrated + testosterone replacement group (n = 10), castrated group (n = 10), and control group (n = 10). After 60 days, prostatectomy was performed in all rats and prostatic specimens were analyzed by haematoxylin eosin (HE) staining under microscope. Semi–quantitative analysis was performed by evaluating growth of epithelial structure and loss of fibromuscular stroma. Results were analyzed using ANOVA test method for normally distributed data. The statistical analysis was performed using SPSS. Results: There was significant reversibility in castration + testosterone replacement groups in all prostatic lobes compared with castration groups (p = 0,010).There were 5 rats showing normal structure of prostate gland compared to control groups in all prostatic lobes (50%), and 5 showed hyperplasia in all prostatic lobes (50%). Conclusion: Testosterone deprivation can cause prostatic atrophy. Dominant atrophy was found in ventral and lateral lobes. Testosterone replacement can prevent atrophy in all prostatic lobes regardless of specific prostatic lobes.Keywords: Testosterone deprivation, testosterone replacement, prostatic lobes.